2021
DOI: 10.1111/vcp.12960
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic variables of the Arrau turtle (Podocnemis expansa) under the effects of different anticoagulants and cytologic stains

Abstract: Background:The hematology of turtles of the Amazon, such as the Arrau turtle (Podocnemis expansa), has not been well described in the literature. Referencing how to collect and analyze blood samples is fundamental for the medical practice of these exotic animals. Objectives:The aim of this study was to evaluate the hematologic parameters of Arrau turtles of the Amazon to determine the best anticoagulant (EDTA, citrate, or sodium heparin) and cytologic stain (Giemsa, Quick Panoptic, or Rosenfeld) for use with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The small sample size ( n =30) in our study precluded calculation of formal reference intervals; nevertheless, these results provide a useful starting point for future studies. Although EDTA, used as an anticoagulant in this study, has been associated with hemolysis in some chelonian species (Muro et al 1998; Garcia et al 2021), our samples showed either no or only mild hemolysis; therefore, this probably had little effect on the values measured. We evaluated serum rather than plasma, which has been used in most other chelonian health assessment studies; therefore, it must be remembered that our findings may not be directly comparable to studies with values derived from plasma.…”
Section: Discussionmentioning
confidence: 65%
“…The small sample size ( n =30) in our study precluded calculation of formal reference intervals; nevertheless, these results provide a useful starting point for future studies. Although EDTA, used as an anticoagulant in this study, has been associated with hemolysis in some chelonian species (Muro et al 1998; Garcia et al 2021), our samples showed either no or only mild hemolysis; therefore, this probably had little effect on the values measured. We evaluated serum rather than plasma, which has been used in most other chelonian health assessment studies; therefore, it must be remembered that our findings may not be directly comparable to studies with values derived from plasma.…”
Section: Discussionmentioning
confidence: 65%
“…A pesar de esto, la heparina de sodio utilizada en este estudio mostró resultados favorables al mantener las muestras sanguíneas de todas las especies analizadas en óptimas condiciones para análisis hematológicos. Estos resultados apoyan diferentes reportes donde también se ha usado a la heparina de sodio para la medición de parámetros hematológicos de tortugas de las especies T. scripta elegans, T. dorbingyi, Podocnemis expansa, Chelonoidis chathamensis, Caretta caretta y Geochelone radiata (11,29,30,31,32,33) semiárido nordestino brasileiro, visando estabelecer valores sanguíneos básicos de saúde e gerar dados úteis na fisiologia comparativa de Testudines. Após 120 dias de adaptação e jejum de 24 horas, 2,5 mL de sangue foram coletados do seio occipital dorsal e depositados em tubo com heparina sódica para a avaliação, na sequência, dos níveis hematologicos.…”
Section: Discussionunclassified
“…A contagem total de eritrócitos (CTE. A diferencia del EDTA, la heparina actúa inhibiendo la trombina, por lo cual se disminuye el riesgo de hemólisis a causa del secuestro del calcio; sin embargo, se ha reportado que este anticoagulante puede interferir con tinciones Romanowsky, al promover la aglutinación de trombocitos y leucocitos, así como generar un efecto azulado en los extendidos (24,33). Así mismo, tras 12 horas de almacenamiento, las células sanguíneas de C. carbonaria mostraron una leve alteración morfológica, lo cual puede estar acentuado por el lapso y los efectos de la heparina en la tinción usada.…”
Section: Discussionunclassified
“…Blood was equally distributed into a 0.5-ml lithium-heparin test tube (BD Microtainer®, Becton, Dickinson and Company, Franklin Lakes, NJ, USA) and a 0.5 ml plain tube (BD Microtainer, Becton, Dickinson and Company) and kept on an ice pack in a cooler box until processing. Smears of whole blood, without anticoagulant (Garcia et al ., 2021), were also obtained and kept at ambient temperature. All blood samples were processed within 2 h of collection.…”
Section: Methodsmentioning
confidence: 99%